PENGEMBANGAN MODUL BERBASIS PBL TERINTEGRASI PISA MATERI BANGUN RUANG SISI LENGKUNG - Pratama, Nasya Aprina; Pasaribu, Feri Tiona; Gustiningsi, Tria; Nusantara, Duano Sapta (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
The purpose of this study was to develop and determine the quality of the product in the form of a PBL (Problem Based Learning) Integrated PISA (Programme For International Student Assessment) Module on the Curved Side Space Building material. This type of research is R&D (Research and Development) development research using the Four-D (Define, Design, Develop, Disseminate) development model. The subjects of the study were students of grades IX J and IX K of Secondary School Number 11 Kota Jambi. The research instruments used included validation questionnaire sheets, practicality questionnaire sheets. The product in the form of a PBL-based Module integrated with PISA was declared valid with a percentage of expert assessment of 88.1% in the "very valid" category, which means that the module contains Curved Side Space Building material arranged based on PBL syntax, contains contextual problems integrated with PISA which are indicators of mathematical literacy skills. The results of the assessment based on teacher responses and student responses, the developed module received a practicality percentage of 93.5% with the "very practical" category, which means that the module can be used easily by teachers and students. Meanwhile, analyzed from students' answers to test questions, this module can bring out students' mathematical literacy skills